Internal Jugular Vein and Transverse Sinus Thrombosis as a Complication of a Chronic Ethmoidal Sinusitis - Damelan, Kombate; Komi, ASSOGBA; vinyo, kumako; E. Josué, diatewa; Kokou Mensah, Guinhouya; kossivi, apetse; mofou, belo; agnon ayélola koffi, balogou (Journal of Neurological Research And Therapy, 2017)
Lemierre’s syndrome is rare jugular thrombosis associated with an oropharyngeal infection. The jugular thrombosis is from septic origin. This often happens in young males subjects. We described Lemierre’s syndrome in a 46 year-old man with a chronic ethmoidal sinusitis associated to the left jugular thrombosis extended to the transverse sinus with a partial recanalisation after three months of oral anticoagulant therapy.
Keywords: Lemierre’s syndrome; thrombosis; oropharyngeal infection